2010
DOI: 10.1021/la903924m
|View full text |Cite
|
Sign up to set email alerts
|

Forced and Spontaneous Imbibition of Surfactant Solution into an Oil-Wet Capillary: The Effects of Surfactant Diffusion Ahead of the Advancing Meniscus

Abstract: A previous paper (Hammond, P.; Unsal, E. Langmuir 2009, 25, 12591-12603) reported a simplified model for the flow of a surfactant solution into an oil-wet capillary. Results were computed by neglecting the spreading of surfactant molecules ahead of the moving oil/water meniscus onto the hydrophobic surface. We now present a more thorough version of the theory where such spreading is considered. Both spontaneous and forced imbibitions are studied. As the differential pressure across the capillary increases, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 16 publications
2
37
0
Order By: Relevance
“…3) (as in the case of spontaneous imbibition of a single fluid against vapor). These observations are intuitively correct and agree well with known theoretical predictions [17][18][19]. Deviation from the square-root law at later stages of the rise is related to the decay of the inlet bulk concentration of surfactants, which is considered to be constant in the theoretical studies.…”
Section: Spontaneous Imbibition Driven By Surfactant Adsorptionsupporting
confidence: 87%
“…3) (as in the case of spontaneous imbibition of a single fluid against vapor). These observations are intuitively correct and agree well with known theoretical predictions [17][18][19]. Deviation from the square-root law at later stages of the rise is related to the decay of the inlet bulk concentration of surfactants, which is considered to be constant in the theoretical studies.…”
Section: Spontaneous Imbibition Driven By Surfactant Adsorptionsupporting
confidence: 87%
“…Some research groups reported that surfactant are not only adsorbed onto the solid surface behind the advancing meniscus but also are transported onto the solid surface ahead of the advancing meniscus through the three-phase contact line (Eriksson et al, 2001;Kumar et al, 2003;Kumar et al, 2008). Hammond and Unsal (2010) developed the numerical model on the basis of previous work by considering the mechanism of surfactant transported across the three-phase contact line. Their numerical results showed that advancing velocity of the meniscus is slower than this mechanism is not presented.…”
Section: Wettability Alteration For Enhanced Oil Recoverymentioning
confidence: 99%
“…Following (Hammond and Unsal 2010) the total amount of surfactant in a given element, represented as a concentration, is denoted i and so…”
Section: Transport Of Surfactantmentioning
confidence: 99%
“…In consequence the threshold pressures p i thresh vary over time as the local surfactant concentration changes. Following (Hammond and Unsal 2010) we relate the interfacial tension in element i, σ i , to the local bulk surfactant concentration c i using:…”
Section: Coupling Of Oil-water Displacement and Surfactant Transportmentioning
confidence: 99%